Self-consciousness negatively mediates the positive association between internalized weight bias and weight status in cross-cultural survey and brain imaging study - Nakamura, Yuko; Hayashi, Karin; Maikusa, Norihide (Frontiers in Psychiatry, 2025)
IntroductionWeight bias internalization (WBI), where individuals adopt negative stereotypes about excess weight, is linked to adverse health outcomes. Although prior research indicates associations between WBI, weight status, and psychological factors linked to self-consciousness, these relationships remain unclear. Thus, this study examined these associations and the relationship between brain characteristics and WBI or self-consciousness.MethodsAn online survey was conducted in Japan (n = 1946), South Korea (n = 500), Germany (n = 598), and the United States (n = 580) to assess WBI, self-consciousness, and body mass index (BMI). In Japanese samples, associations between brain structural (n = 120) or functional (n = 30) characteristics and WBI or self-consciousness were explored.ResultsSelf-consciousness negatively mediated the influence of WBI on BMI, varying across countries. Gray matter volume in the precuneus correlated positively with self-consciousness, while the subgenual anterior cingulate cortex (sACC) response to food reward correlated positively with WBI. Functional connectivity between the precuneus and sACC was positively associated with self-consciousness.ConclusionSelf-consciousness may reduce the impact of WBI on BMI, and the precuneus could be related to this self-consciousness effect, providing further insight into the interactions between WBI and self-consciousness.